2021
DOI: 10.1186/s12889-021-10714-y
|View full text |Cite
|
Sign up to set email alerts
|

The opioid crisis is driving mortality among under-served people living with HIV in British Columbia, Canada

Abstract: Introduction Universal provision of effective antiretroviral medication has been essential to reduce mortality, increase longevity, and reduce onward transmission of HIV. This study aims to illuminate persistent threats to the health and longevity of under-served PLWH in British Columbia (BC), Canada. Methods Between 2007 and 2010, 1000 PLWH across BC were enrolled in the Longitudinal Investigation into Supportive and Ancillary health services (LIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The high proportion of participants managing pain with criminalized drugs in our study is concerning as there is an drug toxicity crisis in British Columbia characterized by contamination of the criminalized drug supply. Unintentional overdose now represents the major driver of mortality in PLWH in the province [ 66 ]. While we did not observe an association between pain and overdose, our data are limited to before 2019, after which the annual rate of drug toxicity deaths in British Columbia increased from 19.4 to 42.7 per 100,000 in 2022 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of participants managing pain with criminalized drugs in our study is concerning as there is an drug toxicity crisis in British Columbia characterized by contamination of the criminalized drug supply. Unintentional overdose now represents the major driver of mortality in PLWH in the province [ 66 ]. While we did not observe an association between pain and overdose, our data are limited to before 2019, after which the annual rate of drug toxicity deaths in British Columbia increased from 19.4 to 42.7 per 100,000 in 2022 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible origin of this HIV “death sentence” discourse could be from participants’ previous and ongoing social immersion with persons living with HIV on the more vulnerable end of the social and economic spectra, persons experiencing difficulties with antiretroviral adherence (for instance, because of street entrenchment) such that participants would infer and conclude that HIV treatment prognoses remained poorer. For added perspective, one recent HIV cohort study found that the leading cause of death of persons living with HIV in the province of BC was drug overdose ( Salters et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present opioid epidemic, a “mass poisoning” event on account of an unsafe drug supply ( Tyndall, 2020 ), has been especially harmful for vulnerable populations in BC ( Salters et al, 2021 ), and antagonistic policing practices have been demonstrated to undermine lifesaving overdose prevention services—and exacerbate the risks of overdoses for vulnerable women ( Goldenberg et al, 2020 ). Unsafe occupational environments are powerful factors driving HIV infection risks among sex workers ( Benoit and Millar 2001 ; Shannon et al, 2008 ; Krüsi et al, 2016 ).…”
Section: Sex Work and Hiv Vulnerabilitiesmentioning
confidence: 99%
“…In BC, the illicit drug toxicity has reduced survival gains achieved by combination antiretroviral therapy (ART) among PWH ( St-Jean et al, 2021 ). Recent evidence indicates a shift in mortality patterns among PWH, with non-HIV causes, particularly accidental overdoses, becoming the leading cause of death from 2010 onwards ( Yazdani et al, 2022 , Salters et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising outlook in HIV treatment, healthcare inequities among PWH with complex co-occurring comorbidities – such as OUD – are jeopardizing improved HIV outcomes ( Salters et al, 2021 ). Studies have found that among people who inject drugs and have HIV, OAT independently influenced the HIV cascade of care and the odds of receiving ART were higher among lifetime recipients of OAT compared to non-OAT recipients ( Mazhnaya et al, 2018 , Mlunde et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%